(untitled) (Biocenosis, 2026)
This article presents an innovative educational methodology centered on the use of natural pigments derived from clays to produce watercolors, with the aim of facilitating a comprehensive understanding of soil as a complex and dynamic system. The proposal integrates scientific, pedagogical, and aesthetic components through a multidisciplinary approach and is applied in both formal and informal educational contexts, promoting meaningful learning based on direct experience. Through workshops conducted in universities, libraries, and environmental fairs, fundamental concepts of soil science—such as soil texture, mineralogical composition, and soil color—are introduced using artistic techniques that allow for the visual representation of soil properties. The methodology encourages the participation of students and the general public, fostering conscious observation of the environment and the appropriation of soil-related knowledge through creativity. The processes of soil collection and treatment, watercolor formulation, and educational implementation strategies are described in detail. In addition, qualitative results obtained through participant observation and direct feedback are analyzed. Findings show increased motivation, improved retention of key concepts, and a strengthened perception of soil as a vital resource. This proposal offers a replicable model for environmental education and soil conservation.